Bacteriocin Production in Bacillus cereus Food Isolates with Molecular Detection of cerA gene (Institute of Medico-legal Publications Pvt Ltd, 2020)
Sixty-three Bacillus cereus strains isolated from food samples. All strains were subjected to DNAsequencing for 16S rRNA for identification. 15 strains were registered at GenBank of NCBI and givennew accession numbers. 41.26% of the isolates showed bacteriocinogenicproduction activity against fourbacterial speciesviz,Bacillus cereus, Staphylococcus aureus, Escherichia coli and Salmonella sp. Presenceof cerA gene coding for cericidine(a type of bacteriocin) was detected in 7.69% of the isolates that producedbacteriocin. Bacterionwas precipitated by ammonium sulphate and purified by dialysis. Antimicrobialactivity of precipitated bacteriocin against the four types of bacteria showed the effect on Bacillus cereus andStaphylococcus aureus growth but not on Escherichia coli and Salmonella spp.The produced bacteriocinhas a molecular weight ranging from 47-54 KDa.Estimation of the concentration and physical and chemicalproperties of bacteriocin were also investigated.